Upaya Fifa dalam Melindungi Hak Pekerja Migran di Qatar Menjelang Piala Dunia 2022 - Agustama, Muhammad Farid; Sunarko, Bagus Sigit; Albayumi, Fuat (University of Jember, 2021)
After winning the right to host 2022 World Cup, Qatar is exposed to migrant workers' problems which have attracted attention of the international community. Migrant workers building infrastructure find themselves in a discriminatory and exploitative treatment. Amnesty International identified hundreds of migrant workers employed on the Khalifa Stadium and the Aspire Zone were being subjected to human rights abuses by the companies for which they worked. According to human rights groups, this is a consequence of the kafala system which is very familiar with modern slavery practices. As one of the main actors of the World Cup in Qatar, FIFA recognized its international significance brings a responsibility to influence decision-makers in Qatar. FIFA has also urged Qatari Government to comply the ILO’s core labour standards into labour reforms, and must be introduced quickly with lasting effect. Hence, this research aims to analyze acts taken by FIFA in its efforts to influence policies related to migrant workers in Qatar. Moreover, to analyze the issue, this research will use two theoretical approaches regarding the concepts of domestic structure and international institutionalization. These two concepts are likely to interact in determining the abilility of transnational actors to bring about policy changes